2007
DOI: 10.1097/01.aog.0000253215.79121.75
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Neonatal Outcome in Early- Onset Placental Dysfunction

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
347
5
42

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(437 citation statements)
references
References 27 publications
28
347
5
42
Order By: Relevance
“…During the last few decades, several large studies have been performed to determine which surveillance technique and signs should be used to determine the optimal timing of delivery of a fetus with IUGR in order to achieve the best short‐term outcome27, 28, 29. Recently, studies in which the outcome also includes long‐term neurodevelopment have been performed30, 31, 32, 33.…”
Section: Discussionmentioning
confidence: 99%
“…During the last few decades, several large studies have been performed to determine which surveillance technique and signs should be used to determine the optimal timing of delivery of a fetus with IUGR in order to achieve the best short‐term outcome27, 28, 29. Recently, studies in which the outcome also includes long‐term neurodevelopment have been performed30, 31, 32, 33.…”
Section: Discussionmentioning
confidence: 99%
“…In the MCA, a PI more than 2 SDs above the mean for gestational age was defined as brain sparing, indicating abnormally reduced impedance to flow in the cerebral circulation. 21 Ductus venosus velocity during atrial systole was characterized as forward or absent/reversed. 21 FHR was considered abnormal, if at least 1 of the following patterns was present: less than 2 accelerations of the heart rate to an amplitude of 10 or more beats per minute lasting 15 seconds or more during a period of at least 30 minutes; variability of 5 or fewer beats per minute during a period of at least 60 minutes; and U-shaped (late) decelerations in the heart rate after Braxton Hicks contractions.…”
Section: Study Populationmentioning
confidence: 99%
“…Although elevated umbilical artery resistance has been suspected to be a marker of deteriorating placental health, recent Doppler evaluation of fetal cerebral and venous circulations has amplified this understanding. [9][10][11] The decision to deliver a preterm, intrauterine growth-restricted fetus is a subject of ongoing controversy and debate, wherein the risk of intrauterine compromise needs to be balanced against potential risks of premature delivery. Baschat et al 10 recently showed umbilical artery flow reversal to be a significant predictor of perinatal mortality, bronchopulmonary dysplasia, intraventricular hemorrhage and NEC.…”
Section: Physiology Of Ductal Stealmentioning
confidence: 99%